Tailoring risks and benefits of invasive strategy in patient with non ST elevation myocardial infarction coexist anemia gravis due to active gastrointestinal bleeding - Afifuddin, Mokhammad; Mohammad Saifur Rohman (Heart Science Journal, 2026)
Background: Myocardial infarction needs revascularization and antiplatelet agents. Nonetheless, the use of antiplatelet agents exacerbates hemorrhagic manifestations in individuals with pre-existing gastrointestinal bleeding.  This case involves a patient who suffered from both a myocardial infarction and gastrointestinal hemorrhage. Case Illustration: An 84-year-old man had escalating chest pain for 10 days before to admission, with a history of heart failure for the last 3 years. He also had melena caused by over-the-counter analgesics. The ECG in the emergency department indicated ST elevation in aVR and ST depression in leads I, II, III, aVL, and V4-V6, accompanied with hs-Troponin I levels of 1945 ng/L and hemoglobin at 5 g/dL. He was assessed as high-risk Non ST Eleveation Myocardial Infarction (NSTEMI), with a Grace score of 210, while experiencing severe anemia owing to ongoing gastrointestinal bleeding. The patient received a PRC transfusion, a proton pump inhibitor, and sucralfate syrup. Angiography revealed critical stenosis with thrombus in diagonal one of the left anterior descending artery and significant calcified stenosis in the distal left circumflex artery. Consequently, one drug-eluting stent was inserted in the osteal-distal left anterior descending artery.  The clinical symptom subsequently improved. Aspirin and Clopidogrel were provided post-stent implantation with sequential blood assessments. An endoscopy was also conducted to assess  bleeding source. Conclusion: A patient with NSTEMI and severe anemia owing to active gastrointestinal bleeding had an invasive approach, during which a drug-eluting stent was placed. Administration of dual antiplatelet therapy must be carefully managed.